A Pyrone and Flavonoid Derivatives from Cryptocarya crassinervia and their Inhibitory Properties against Receptor Tyrosine Kinases - Dian Nugraheni; Elvira Hermawati; Hendra Helmanto; Dikhi Firmansyah; Yana Maolana Syah; Lia Dewi Juliawaty (Directorate for Research and Community Services (LPPM) ITB, 2024)
A new a-pyrone, i.e., cryptocrassinervione (1), and a new flavone glycoside, i.e., kaempferol-3-O-rhamnosyl-2-O-apiofuranoside (4), were isolated from EtOAc extract of Cryptocarya crassinervia leaves. Along with these compounds, two known flavone glycosides, namely afzelin (2) and quercitrin (3), were also isolated. The structures of the new compounds were determined based on NMR and mass spectral data. Compounds 1–4 were examined against eight receptor tyrosine kinases (RTKs) (EGFR, HER2, HER4, IGF1R, InsR, KDR, PDGFRα, and PDGFRβ), which showed that these compounds were moderately active against EGFR, with inhibition percentages of 55, 49, 41, and 44%, respectively. They were weakly active against HER2, with inhibitions of 17, 20, 18, and 16%, respectively. However, they were not active against the rest of the RTKs. Nevertheless, compounds 1–4 have potency as inhibitors of EGFR.